Convenient synthesis of amides by Zn(ClO4)2·6H2O catalysed Ritter reaction with nitriles and halohydrocarbons. (July 2018) - Feng, Chengliang; Yin, Guibo; Yan, Bin; Chen, Junqing; Ji, Min
A convenient and high yielding procedure for the synthesis of amides by the Ritter reaction of nitriles and halohydrocarbons in the presence of Zn(ClO4 )2 ·6H2 O as a highly stable, effective and available catalyst is described.